Discovery of a pyrrole-pyridinimidazole derivative as novel SIRT6 inhibitor for sensitizing pancreatic cancer to gemcitabine - Nannan Song; Xian Guan; Siqi Zhang; Yanqing Wang; Xuekai Wang; Zhongxia Lu; Daochen Chong; Jennifer Yiyang Wang; Rilei Yu; Wengong Yu; Tao Jiang; Yuchao Gu (Cell Death and Disease, 2023)
Abstract Pancreatic cancer is a highly aggressive cancer, and is primarily treated with gemcitabine, with increasing resistance. SIRT6 as a member of sirtuin family plays important roles in lifespan and diverse diseases, such as cancer, diabetes, inflammation and neurodegenerative diseases. Considering the role of SIRT6 in the cytoprotective effect, it might be a potential anticancer drug target, and is associated with resistance to anticancer therapy. However, very few SIRT6 inhibitors have been reported. Here, we reported the discovery of a pyrrole-pyridinimidazole derivative, 8a, as a new non-competitive SIRT6 inhibitor, and studied its roles and mechanisms in the antitumor activity and sensitization of pancreatic cancer to gemcitabine. Firstly, we found a potent SIRT6 inhibitor compound 8a by virtual screening and identified by molecular and cellular SIRT6 activity assays. 8a could effectively inhibit SIRT6 deacetylation activity with IC50 values of 7.46 ± 0.79 μM in FLUOR DE LYS assay, and 8a significantly increased the acetylation levels of H3 in cells. Then, we found that 8a could inhibit the cell proliferation and induce cell apoptosis in pancreatic cancer cells. We further demonstrate that 8a sensitize pancreatic cancer cells to gemcitabine via reversing the activation of PI3K/AKT/mTOR and ERK signaling pathways induced by gemcitabine and blocking the DNA damage repair pathway. Moreover, combination of 8a and gemcitabine induces cooperative antitumor activity in pancreatic cancer xenograft model in vivo. Overall, we demonstrate that 8a, a novel SIRT6 inhibitor, could be a promising potential drug candidate for pancreatic cancer treatment.